The Cut-Score Operating Function: A New Tool to Aid in Standard Setting. (June 2017) - Grabovsky, Irina; Wainer, Howard
In this essay, we describe the construction and use of the Cut-Score Operating Function in aiding standard setting decisions. The Cut-Score Operating Function shows the relation between the cut-score chosen and the consequent error rate. It allows error rates to be defined by multiple loss functions and will show the behavior of each loss function. One strength of the Cut-Score Operating Function is that it shows how robust error rates are to the choice of cut-score and identifies the regions of extreme sensitivity relative to that choice.